Evaluating Technology-Enhanced, STEAM-Based Remote Teaching With Parental Support in Luxembourgish Early Childhood Education - Haas, Ben; Lavicza, Zsolt; Houghton, Tony; Kreis, Yves (Frontiers in Education, 2022)
During COVID-19 confinement, we observed numerous challenges in using educational technology in early childhood STEAM education in Luxembourg. Thus, we designed a conceptual framework on parent-assisted remote teaching with active uses of educational technology supported by cycles of design-based research. After a previous study utilising Computer-Aided Design (CAD) software and 3D printing in primary education, we used our initial findings to work with 12 early childhood students (ages 4-6), together with their teachers and parents in the second remote teaching period in Luxembourg. We created a STEAM modelling task with CAD software on robots and collected data through chat responses, messageboards, and online communication channels during a three-week period. Here, we observed new roles in the parent-child relationship while learning STEAM in remote teaching with technology, and new opportunities in using educational technology overall in early childhood education. In this paper, we will describe findings that are likely to influence students’ learning and parents assisted teaching, in particular parents and students’ perceptions and motivations, together with the way in which parents provide technical knowledge and support in in remote early childhood STEAM education.